Effect of Modified Lemaire Anterolateral Extra-articular Tenodesis on the Magnetic Resonance Imaging Maturity Signal of Anterior Cruciate Ligament Hamstring Graft. Issue 9 (July 2021) - Rojas, Gonzalo; Perelli, Simone; Ibanez, Maximiliano; Formagnana, Mario; Ormazabal, Inmaculada; Monllau, Juan Carlos
Background: Lateral extra-articular tenodesis (LET) is one of the most widely used procedures to restore anterolateral stability. Clinical outcomes after the addition of LET to anterior cruciate ligament (ACL) reconstruction (ACLR) have been widely investigated; however, the potential influence of LET on the ACL ligamentization process has not been examined. Purpose/Hypothesis: The purpose was to use 10-month postoperative magnetic resonance imaging (MRI) scans to determine whether the maturity of grafts after hamstring autograft ACLR was affected by concomitant LET. The hypothesis was that when modified Lemaire lateral extra-articular tenodesis (MLLET) was performed, the MRI parameters of ACL graft maturity would be modified. Study Design: Cohort study; Level of evidence, 3. Methods: The study included patients treated between December 2017 and December 2018 who had undergone anatomic 3-strand hamstring tendon autograft ACLR, with or without concomitant MLLET, and had undergone MRI 10 months postoperatively. Thus, the study included 30 patients who had isolated ACLR and 22 patients who had ACLR plus MLLET. The 2 groups were comparable based on all criteria analyzed. To evaluate graft maturity, the signal-to-noise quotient (SNQ) was measured in 3 regions of interest of the proximal, midsubstance, and distal ACL graft. Lower SNQ ratios indicate less water content and, theoretically, better maturity and healing of the graft. Results: The mean ± SD for SNQ was 4.62 ± 4.29 (range, 3.12-6.19) in the isolated ACLR group and 7.59 ± 4.68 (range, 4.38-8.04) in the ACLR plus MLLET group ( P = .012). Upon comparing the mean values of the 3 portions between the 2 groups, we found a significant difference between the 2 groups for the proximal and middle portions ( P = .007 and P = .049, respectively) but no difference in the distal portion ( P = .369). Conclusion: At the 10-month follow-up, hamstring tendon autografts for anatomic ACLR with MLLET did not show the same MRI signal intensity compared with isolated hamstring anatomic ACLR.